Characteristics of Low Back Pain in Medical Students of Muhammadiyah Jakarta University Class of 2019 After Online Class for One Semester - Rizkiandini, Sulfa; Hamzah, Zainy (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2023)
Introduction: Lower back pain (LBP) is a complaint that is often felt by everyone in everyday life. In 2010 the Global Burden of Disease Study estimated low back pain to be one of the top ten diseases and injuries with the highest number in the world. According to research conducted by Altinel in 2008, about 62% of adults experience LBP as a result of sitting too long in the wrong position. The wrong sitting attitude of someone at work will affect the unfavorable results of their work. Method: This research is a descriptive analytic survey research, which aims to know about low back pain ofÂ  the students of the Medical Education Study Program Class of 2019. approach used in this study is "cross sectional study", with a total sample of 113 respondents. Result: From the 113 respondents the results of research conducted through a questionnaire, there were 59 respondents (52.2%) who were researched having a low back pain. In the category based on the length of study, 59 respondents (52.2%) experienced LBP complaints and the results of statistical analysis (P = 0.030) where there was a significant relationship between the length of study and LBP complaints. In the category of the relationship between sitting position when doing online, there were 59 respondents (52.2%) and the results of statistical analysis (P = 0.526), there was no significant relationship in the position category when doing online with LBP complaints and in the sitting position category when learning was obtained 59 respondents (52.2%) and the results of statistical analysis (P = 0.183), namely that there was no significant relationship in the category of learning position with LBP complaints. Conclusion: There is no significant relationship between learning position and length of study with complaints of low back pain in students of 2019 Medicine Program of Muhammadiyah Jakarta University. Because, the improper sitting position and duration of study are not solely factor that lead to low back pain.